Exploration on self-equilibrium rule and adsorption-desorption model between pine nut (Pinus koraiensis) peptide molecules and environmental moisture molecules. (June 2020) - Yang, Ruiwen; Ju, Huapeng; Yuan, Liyan; Ye, Haiqing; Lin, Songyi
Graphical abstract: Highlights: Found the adsorption rule between moisture molecules and peptide molecules. Explored the sorption isotherms type and water self-equilibrium rule of peptide. Built the optimal adsorption-desorption model of PNP powder. Optimized adsorption model for PNP powder changed from Henderson to Oswin model. Optimized desorption model for PNP powder changed from Halsey to GAB model. Abstract: The storage of pine nut ( Pinus koraiensis ) peptide (PNP) powder involves hygroscopic phenomena. To investigate the adsorption and self-equilibrium rules between these peptides and the environmental moisture molecules, several studies such as low-field nuclear magnetic resonance (LF-NMR), dynamic vapor sorption (DVS) and adsorption-desorption models were done. The results showed that the outward moisture migration occurred during storage as 7.80% and 16.68% moisture were respectively constrained by the original sample and 90 days after lyophilization, by chemical bonding. Additionally, 1.79% moisture was lost in PNP powder at day 90. The optimized adsorption model for PNP powder was changed from Henderson's to Oswin's model during the 90 days' storage whereas the optimized desorption model was changed from Halsey's to GAB's model. The PNP powder at day 90 presented smaller particles with an average diameter and height of 15.645 nm and 50 nm, respectively, and it contained more molecular moisture which cannot be removed. The free thiol of the PNP powder at day 0 and day 90 was 1.75 ± 0.16 μM SH/g and 1.95 ± 0.16 μM SH/g, respectively, and the total sulfhydryl was 101.46 ± 1.06 μM SH/g and 118.44 ± 1.27 μM SH/g. The registered increased sulfhydryl content contributed to the generation of off-flavor.